Peningkatan Kapasitas Pengelolaan Keuangan Usaha Skala Mikro Menuju Bisnis Digital Kompetitif - Tugiantoro Tugiantoro; Ida Adhani; Yustinus Rawi Dandono; Wedia hastuti; Rida Justin Jacobalis; Desika Andriani (Universitas Dehasen Bengkulu, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy but are often hampered by weak financial management systems. In the Pesanggrahan area, some MSME actors still mix personal and business funds and do not understand the preparation of standardized financial reports. This Community Service (PKM) activity aims to provide solutions to these problems through business financial management training and 'scale-up' strategies towards a competitive business. The method used is interactive socialization and mentoring (workshop) attended by 18 MSME actors out of 30 invitees. The results showed an increase in participants' understanding of the importance of financial separation, recording based on Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), and utilizing financing access such as People's Business Credit (KUR). It is hoped that this activity can encourage Pesanggrahan MSMEs to scale up and become more bankable.